2012
DOI: 10.1093/jac/dks276
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the potential for resistance development to ceragenin CSA-13

Abstract: CSA-13 retained potent antibacterial activity against S. aureus over the course of 30 serial passages. Resistance generated in Gram-negative bacteria correlates with modifications to the outer membranes of these organisms and was not stable outside of the presence of the antimicrobial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
61
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 35 publications
8
61
0
1
Order By: Relevance
“…For example, ceragenins retain activity against methicillin-resistant Staphylococcus aureus, [21] colistin-resistant Klebsiella pneumoniae [22,23] and fluconazoleresistant Candida albicans [24] Efforts to generate resistance to selected ceragenins have resulted in relatively small changes in susceptibility, due to modifications of the lipid A portion of LPS, but high levels of resistance have not been observed [22,25]. Multiple in vivo studies have demonstrated that ceragenins are well tolerated in specific tissues and retain their antibacterial activities [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ceragenins retain activity against methicillin-resistant Staphylococcus aureus, [21] colistin-resistant Klebsiella pneumoniae [22,23] and fluconazoleresistant Candida albicans [24] Efforts to generate resistance to selected ceragenins have resulted in relatively small changes in susceptibility, due to modifications of the lipid A portion of LPS, but high levels of resistance have not been observed [22,25]. Multiple in vivo studies have demonstrated that ceragenins are well tolerated in specific tissues and retain their antibacterial activities [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high antibacterial activity, CSA-13 is the most promising ceragenin. A recent finding showed that CSA-13 retained potent antibacterial activity over the course of 30 serial passages, indicating that bacteria are very unlikely to develop resistance against this compound (10). In addition to bactericidal activity against planktonic bacteria, CSA-13 disintegrates bacterial biofilms in a very efficient manner, at a concentration slightly higher than that required for bactericidal activity against planktonic bacteria (11,12).…”
mentioning
confidence: 99%
“…This has led to many AMPs, such as pexiganan (analogue of magainin), gramicidins, polymyxin, nisin, daptomycin, and defensin-mimetic molecule, being entered into clinical trials (2)(3)(4)(5)(6). However, it has been argued in several in vitro studies and recent reports that the use of AMPs in therapeutic amounts over an extended period of time might lead to reduced susceptibility due to adaptive changes in phenotypic and genotypic characteristics of the organism (7)(8)(9)(10)(11)(12)(13). Therefore, the aim of our study was to examine whether S. aureus bacteria, on continuous exposure to sublethal concentrations of certain well-studied AMPs (magainin 2 and gramicidin D), alter their susceptibility and whether resistant strains are selected.…”
mentioning
confidence: 99%